Simulation and experimental study of mechanical and fracture behavior of 2.5D woven C‐fiber/aluminum composites under warp directional tension loading. Issue 2 (9th November 2020) - Wang, Zhenjun; Wang, Zhongyuan; Liu, Yong; Cai, Changchun; Xiong, Bowen; Wang, Zhitai; Xu, Zhifeng; Yu, Huan
Abstract: The mechanical and fracture behavior of innovative 2.5D woven fabric/aluminum composites under warp directional tension were investigated via micromechanical simulation and experiments. The tensile curves from the simulation correspond well with the testing curves, where calculation errors of the elastic modulus, ultimate strength, and fracture strain are 3.96%, 1.40%, and −5.49%, respectively. The warp yarn interface and neighboring matrix are damaged during the initial tension process. The accumulation and interaction of these damage zones lead to successive failures of the interface, matrix, and weft yarns. The axial fracture of warp yarns ultimately induces failure of the composite, which exhibits transverse crack of weft yarns with interfacial debonding and axial fracture of warp yarns with fiber pulling out. The elastic modulus and ultimate strength increased with an increase in the weft yarn layer spacing or a decrease in the warp yarn layer spacing, whereas the fracture strain decreased with an increase in the layer spacing of the warp or weft yarns.